2022
DOI: 10.1136/bcr-2022-248785
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal hepatic small vessel neoplasm with spleen dissemination

Abstract: Among liver vascular tumours, hepatic small vessel neoplasm (HSVN) has been recently identified as a rare infiltrative vascular neoplasm whose malignant potential is yet to be fully ascertained. About 30 cases of HSVN have been described so far. The most common clinical presentation is an asymptomatic solitary liver lesion. Multifocal disease has been described in literature; however, to date, there are no reports of disease dissemination to other organs. Here we report a case of multifocal HSVN with synchrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Treatment strategies range from complete resection 2 to regular 6-month surveillance imaging. 8 This case reinforces the importance of integrating clinical data, such as serum PSA levels, as well as the distribution of uptake before concluding focal 18 F-DCFPyl uptake represents metastatic disease.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Treatment strategies range from complete resection 2 to regular 6-month surveillance imaging. 8 This case reinforces the importance of integrating clinical data, such as serum PSA levels, as well as the distribution of uptake before concluding focal 18 F-DCFPyl uptake represents metastatic disease.…”
supporting
confidence: 57%
“…As 18 F-DCFPyl has been shown to accumulate at sites of increased or abnormal vascular proliferation, 1,6,7 it is possible that increased 18 F-DCFPyl uptake is another imaging feature of HSVNs and could explain the finding on this patient's prostate-specific membrane antigen PET/CT. Treatment strategies range from complete resection 2 to regular 6-month surveillance imaging 8 . This case reinforces the importance of integrating clinical data, such as serum PSA levels, as well as the distribution of uptake before concluding focal 18 F-DCFPyl uptake represents metastatic disease.…”
mentioning
confidence: 57%
“…Goh et al, in their meta-analysis, demonstrated a male predominance with a male-to-female ratio of 2,8:1 with a median age of 58 years (range 24-83). The majority of cases involved solitary lesions; five patients exhibited multiple lesions [ 2 , 4 , 5 ], while Cicala et al [ 5 ] reported possible disease dissemination to the spleen. The size of the tumors ranged from 10 mm to 159 mm, with a median size of 27.8 mm at its greatest diameter.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by strong expression of vascular markers (CD31, CD34, FLI-1, and ERG) and is pancytokeratin negative. All cases have a low Ki-67 proliferation index (<10%) [ 4 ]. Next-generation sequencing has shown activating hotspot mutations in the alpha subfamily of G-proteins (GNAQ, GNA11, and GNA14) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD31 and CD34 are positive. Ki-67 levels are higher with a mean of 42.8% [ 3 , 4 ]. Thus, the Ki-67 proliferation index can be a useful distinction in differentiating these two neoplasms.…”
Section: Discussionmentioning
confidence: 99%